“Gestión del talento humano y su efecto en las relaciones laborales de los empleados de la rectificadora “Motores Suarez” - Palma Manobanda, Odalis Ivonne (2025)
In today's competitive marketplace, companies like Rectificadora Motores Suarez, an engine grinding company, require sound human talent management strategies to thrive. Effective talent management not only fosters employee development and retention, but also improves labor relations, creating a favorable working environment for achieving organizational goals. However, despite largely complying with mandatory compensation benefits and receiving a fair wage policy, they face the challenge of optimizing their human talent management practices to maximize their impact on interpersonal relationships. Initial findings reveal that while formal compensation is in line with the law, significant weaknesses persist in internal communication, conflict management and fostering collaboration, with many employees feeling uncomfortable expressing opinions or perceiving inconsistencies in encouraging open dialogue and recognition of their contributions to the team. The research focuses on determining the effects of human talent management practices on employee labor relations at Rectificadora Motores Suarez, using a mixed sequential qualitative-quantitative methodology. Methods such as deductive, inductive and explanatory will be used, combining quantitative data collection through surveys and qualitative data collection through semi-structured interviews. The research instruments include Likert scale questionnaires and semi-structured interviews, validated through previous research and recognized methodological proposals. The study concludes that, beyond economic compensation, Rectificadora Motores Suarez needs to improve its strategies to address negative perceptions about the physical work environment and strengthen the connection between professional development and improved collaboration, thus fostering a more equitable, satisfying and collaborative work environment.